Estimating porosity from CT scans of high permeability core plugs - Squelch, Andrew; Harris, Brett; AlMalki, Majed (CSIRO, 2012)
We have analysed CT scans of core plugs obtained from high permeability sandstones in the Wanneroo Sandstone member of the Leederville formation in the Perth Basin. Plugs taken from drill core at representative sections of aquifer horizons have been scanned in a SkyScan CT scanner and the resulting greyscale image stacks analysed to estimate hydraulic transport parameters of the aquifer horizon. These parameters are compared with laboratory measured porosity and permeability values obtained from standard physical tests. The analysis of the CT data provides support for understanding parameters derived from standard core plug analysis and wire line logging. However it also allows for a localised study of different zones within the core plug volume that is not possible with more ‘holistic’ laboratory measurement. Also, the mechanical framework of the grain and pore structure can be extracted as 3D geometric models for additional types of analysis and numerical modelling. We estimate values for porosity and permeability for distinct zones within the core plugs and for the full width of the core plug. The full width values are compared with the equivalent laboratory values and for calibration. In addition, the possible impact of millimetre to centimetre zonation for grain size and shape distribution is considered with reference to anisotropy in larger scale physical measurements from wire-line logging.